2014
DOI: 10.1080/20430795.2013.837808
|View full text |Cite
|
Sign up to set email alerts
|

An equation with many variables: unhiding the relationship between sustainability and investment performance

Abstract: Financial investment performance of stock portfolios is driven by many factors of influence like portfolio diversification, quality of funds management or gravitational effects of market phases. It is, therefore, quite possible that relationships between sustainability and financial performance elude measurability because they may be overshadowed and dominated by other, more powerful or temporarily more influential factors. Using a new quantitative model for portfolio optimisation that simultaneously controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Instead of relying on a risk and return-oriented decision, they pursue several investment objectives simultaneously. Multi-dimensional optimizations have been applied to various criteria (e.g., portfolio size, transaction costs or aspects of taxation) [61]. The integration of corporate sustainability was proposed by Peylo [62] with a three-dimensional optimization framework.…”
Section: Integrating a Composite Sustainability Index Into Project Pomentioning
confidence: 99%
“…Instead of relying on a risk and return-oriented decision, they pursue several investment objectives simultaneously. Multi-dimensional optimizations have been applied to various criteria (e.g., portfolio size, transaction costs or aspects of taxation) [61]. The integration of corporate sustainability was proposed by Peylo [62] with a three-dimensional optimization framework.…”
Section: Integrating a Composite Sustainability Index Into Project Pomentioning
confidence: 99%
“…The entirely opposite results were obtained by Peylo and Schaltegger [68] and Gasser et al [54]. Peylo and Schaltegger [68] investigated whether and to what extent different levels of sustainability in stock portfolios impact investment return when other factors with known influence on investment performance are neutralized. Their findings showed a clear nonlinear relationship between sustainability and investment performance.…”
Section: Resultsmentioning
confidence: 80%
“…The existing literature examining the relationship between sustainability and a portfolio's financial return is undecided. Most studies compare the financial performance of socially responsible investment (SRI) portfolios with that of traditional portfolios [51,54,58,60,66,68,97]. Bilbao-Terol et al [60] showed that investor's attitudes towards risks affect the loss of return which is conditioned by choosing SRIs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate on the superiority of green vis-a-vis sin investments has continued unabated [Statman, 2000, Schroder, 2004, Cui, 2007, L opez et al, 2007, Fabozzi et al, 2008, Renneboog et al, 2008, Hong and Kacperczyk, 2009, Kim and Venkatachalam, 2011, P erez-Gladish et al, 2013, Nofsinger and Varma, 2014, Peylo and Schaltegger, 2014, Leite and Cortez, 2015, Junkus and Berry, 2015, Trinks and Scholtens, 2017, Garvey et al, 2018, Duran-Santomil et al, 2019, Chang et al, 2019, Bolton and Kacperczyk, 2021, Rehman et al, 2021, Aswani et al, 2022, Blitz and Swinkels, 2021, P astor et al, 2022, Vymyatnina and Chernykh, 2022.…”
Section: Introductionmentioning
confidence: 99%